Traumatic diaphragmatic rupture in children - W. Burhamah; M. Matcovici; A. Hardy; S. Awadalla (Elsevier, 2020)
Introduction: Traumatic diaphragmatic ruptures (TDR) are rare in children and when present are usually associated with polytrauma. Due to the non-specific signs in acute setting and to the occurrence with other main organ injuries, the diagnosis of TDR is often missed. The few reported cases in the literature are showing a high incidence of delayed diagnosis leading to increased morbidity and mortality.We present the case of a boy who was admitted after being run over by a lorry and an early diagnosis of TDR was made. An initial Chest X-ray showed a right elevated hemidiaphragm raising the possibility of TDR. A misleading diagnosis of pleural effusion led to insertion of a chest drain with no significant consequences. A repeated CT confirmed the TDR diagnosis and the patient was taken to theatre the same day for surgical repair. He had an eventful recovery and he was discharged 28 days postoperatively. Conclusion: The diagnosis of TDR remains a challenging clinical and imaging entity. A very high index of suspicion is required in the scenario of a polytrauma patient, especially in victims of blunt abdominal trauma.